2020
DOI: 10.4041/kjod.2020.50.6.407
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dental phenotypes and treatment modalities in Korean patients with Parry–Romberg syndrome

Abstract: Objective: To investigate the dental phenotypes and treatment modalities (Tx-Mod) in Korean patients with Parry-Romberg syndrome (PRS) using longitudinal data. Methods: The samples consisted of 10 PRS patients, who were treated and/or followed-up at Seoul National University Dental Hospital between 1998 and 2019. Using a novel PRS severity index based on the numbers of the atrophy-involved area and asymmetry-involved item, we classified them into mild (n = 3), moderate (n = 2), and severe (n = 5). Dental pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…The Cleft Palate Craniofacial Journal 60 (8) beginning dental and orthodontic treatment at an earlier age among this patient population. This study corroborates previous studies noting the possibility of tooth hypoplasia 13,14,16,17,19,21,23,24 , agenesis 15,23 and delayed eruption 14,16,17,20,23,24 in patients with Parry-Romberg Syndrome. Providers should consider these anomalies in their evaluation, planning, and treatment of patients with Parry-Romberg Syndrome.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The Cleft Palate Craniofacial Journal 60 (8) beginning dental and orthodontic treatment at an earlier age among this patient population. This study corroborates previous studies noting the possibility of tooth hypoplasia 13,14,16,17,19,21,23,24 , agenesis 15,23 and delayed eruption 14,16,17,20,23,24 in patients with Parry-Romberg Syndrome. Providers should consider these anomalies in their evaluation, planning, and treatment of patients with Parry-Romberg Syndrome.…”
supporting
confidence: 92%
“…There are a number of oral health concerns in Parry-Romberg Syndrome, reported primarily in small series documenting findings that involve soft tissue (ie tongue atrophy, gingival exposure, lip incompetence), the jaws (ie temporomandibular joint dysfunction, malocclusion), and teeth (ie agenesis, delayed eruption, and root atrophy). [13][14][15][16][17][18][19][20][21][22][23][24] The aim of this study was to review the dental findings in patients with Parry-Romberg Syndrome treated at our institution over the past four decades to document anomalies noted in this patient population, to identify situations in which early referral may help prevent worse dental outcomes, and to inform multidisciplinary care for this patient population. This is the largest study of dental anomalies in Parry-Romberg Syndrome reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…8 Dental phenotypes generally involve root resorption, tooth curvature and cracks, etc. 9 Glandular features include reduced salivary gland secretion, dry mouth, and atrophy of half tongue. 10 A few cases are accompanied with vitiligo, scleroderma, intracranial aneurysm, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Travma, enfeksiyon, genetik faktör, epilepsi, migren, trigeminal nevrit, lenfositik nörovaskülit, lokalize skleroderma, endokrin bozukluğu, otoimmünite, sempatik sinir sisteminin hiper-veya hipo-aktivitesi ve serebellumun yağ metabolizmasında bozukluk gibi çok sayıda neden ileri sürülmüştür. 11,12 Az sayıda hastada vitiligo, tiroid sorunları, sistemik skleroz, inflamatuar barsak hastalığı, romatoid artrit, ankilozan spondilit, sistemik lupus eritematozus ve multipl skleroz gibi diğer otoimmün bozukluklar da rapor edilmiştir. Eşlik eden ağız ve çevre dokularında alın, yanaklar, çene, dudaklar, dişler, diş etleri ve dil tutulumu görülmüştür.…”
unclassified